The performance of real estate private equity funds in South Africa - Omar, Zain (My University, 2020)
Using a sample of seven real estate private equity funds in South Africa, we firstly investigate the actual performance of these funds relative to their targeted returns at inception, and the performance of the market over the holding period. Results indicate that South Africa’s REPE funds were able to meet and surpass their targeted returns, including those that were promised to prospective clients during the prospectus stages. Furthermore, REPE performed above market expectations and were able to exceed market returns.
A research report submitted in fulfilment of the requirements for the degree of Masters of Management in Finance and Investment (MMFI) to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2020
Keywords: REAL ESTATE; PRIVATE EQUITY; EQUITY FUNDS; SDG-8: Decent work and economic growth